Improving Nanoparticle Drug loading: Matching Polymer to Drug Properties and making of Polymer coated Drug Nanoparticles - ANIMASAWUN, R.K (2020)
Poor Central Nervous System (CNS) penetration by cancer drugs limits their application in brain tumours, such as medulloblastoma. An alternative approach, delivering anticancer drugs directly to residual tumour using nanoparticulate delivery systems (NPDS) could reduce some of these problems. The main challenges hindering the clinical translation of the use of NPDS for local delivery of drugs to the residual tumour are inadequate drug loading and erratic release. This study focusses on understanding the conditions required for the development of a NPDS with sufficient drug loading for post-surgical delivery to the residual tumour. Known effective drugs; Etoposide, Etoposide phosphate and Teniposide were screened against modified poly(glycerol) adipate based polymers. This was done by monitoring drug release from 40% drug-polymer loaded films and using Fourier Transform Infra-Red spectroscopy (FTIR) and contact angle measurements to explain the release results. Polymers of different structure were then matched with the specific drugs based on the interactions observed to prepare drug loaded nanoparticles. Two types of drug loaded nanoparticles were prepared from these combinations. Drug loaded matrix polymer nanoparticles (NP) were prepared by an interfacial deposition method, while a novel process of applying a polymer coating to drug nanoparticles, termed polymer coated drug nanoparticles (PCDNP), was also developed. The nanoparticles were characterised applying physicochemical characterisation methods, and their cytotoxicity assessed. The key benefits of this work are the development of a systematic method to match polymers to drugs through assessing drug and polymer interactions, resulting in the formulation of nanoparticles with higher drug loading, and secondly the development of a novel technique of making nanoparticles, polymer coated drug nanoparticles (PCDNP).